Miniscrew-assisted rapid palatal expander (MARPE): the quest for pure orthopedic movement - Suzuki,Hideo (2016)
ABSTRACT The midpalatal suture has bone margins with thick connective tissue interposed between them, and it does not represent the fusion of maxillary palatal processes only, but also the fusion of palatal processes of the jaws and horizontal osseous laminae of palatal bones. Changing it implies affecting neighboring areas. It has got three segments that should be considered by all clinical analyses, whether therapeutic or experimental: the anterior segment (before the incisive foramen, or intermaxillary segment), the middle segment (from the incisive foramen to the suture transversal to the palatal bone ) and the posterior segment (after the suture transversal to the palatal bone ). Rapid palatal expansion might be recommended for patients at the final pubertal growth stage, in addition to adult patients with maxillary constriction. It represents a treatment solution that can potentially avoid surgical intervention. When performed in association with rapid palatal expanders, it might enhance the skeletal effects of the latter. Of the various designs of expansion appliances, MARPE (miniscrew-assisted rapid palatal expander) has been modified in order to allow its operational advantages and outcomes to become familiar in the clinical practice.